Histopathologic Effects of Dirofilaria immitis Microfilaria on Internal Organs of Dog Confirming by PCR Technique - Ceribasi, A. O.; Simsek, S. (Iranian Scientific Society Medical Entomology, 2012)
Background: The heartworm disease is an infectious disease of dogs with Dirofilaria immitis combined with cardiovascular and circulatory abnormalities. The heartworm disease can become a serious health risk when associated with a severe infection. In this study, a male, 8 year-old dog that died suddenly was necropsied and all tissues were examined grossly. Methods: Major organs including heart, lungs, liver, spleen, kidneys, brain, eyes, and testis were fixed in 10% neutral formalin, embedded in paraffin, sectioned at 5-mu m thickness, stained with hematoxylin and eosin, and examined with a light microscope. For each examined organ, paraffin-embedded tissues were cut and placed in eppendorf tubes for genomic DNA extraction. PCR was performed using two sets of primers for amplification of a 302 bp ITS-2 gene fragment and a 203 bp cytochrome oxidase subunit 1 (CO1) gene fragment of D. immitis. Results: During the necropsy examination, 46 adult D. immitis were found in the portal vein, right ventricle, and atrium of the heart and pulmonary trunk. Microscopically, microfilarias were found throughout the vessels of different organs including lungs, kidneys, liver, heart, brain, and spleen. All tissues examined by PCR were positive for D. immitis ITS-2 and CO1. Conclusion: PCR technique now represents an effective method for identification of D. immitis from formalin-fixed samples.
Keywords: Dirofilaria immitis; PCR; Histopathology; Paraffin; Dog